Wrongful life: some of the problems. Issue 2 (June 1987) - Liu, A N
Abstract : The author considers that some of the reasonings used by both the American and English courts against recognising a wrongful life claim are far from persuasive. However, there may indeed be strong public policy reasons against judicial recognition of such a claim. If judicial remedy is not possible for children in wrongful life situations, society ought to assist them in the alleviation of some of the practical problems caused by deformities.